2021
DOI: 10.5713/ajas.20.0292
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone exposure affects the Wnt/β-catenin signaling pathway and related genes of porcine endometrial epithelial cells in vitro

Abstract: Objective: ZEA has estrogen-like effects. Our previous study has shown that ZEA (0.5-1.5 mg/kg) could induce abnormal uterine proliferation through TGF signaling pathway. In order to further study the other regulatory networks of uterine hypertrophy caused by ZEA, the potential mechanism of ZEA on porcine endometrial epithelial cells was explored by the Illumina Hiseq 2000 sequencing system in this study. Methods: The PECs were treated with ZEA at 0 (ZEA0), 5 (ZEA5), 20 (ZEA20), and 80 (ZEA80) μmol/L for 24 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In mouse ovarian granulosa cells Chen et al [ 96 ] and Zhang et al [ 97 ] demonstrated by MTT, EdU and flow cytometry that ZEA suppressed in vitro cell viability at 30–150 μM and increased apoptosis at 15–60 μM after 24 or 72h of exposure. Close to the results recorded by Song et al [ 95 ] in pig (a decreased of cell proportion in the S and G2 phase at ZEA 80 µmol/L), Zhang et al [ 97 ], found that mouse granulosa cells were arrested in G1 phase of cell cycle and the cells proportion decreased in phase S and G2 after 30 μM ZEA treatment. However, in another study this author [ 98 ] found species specific ZEA effect, pig being more sensitive than mouse.…”
Section: Effect Of Zearalenone On Adaptive Immune Responsesupporting
confidence: 65%
See 2 more Smart Citations
“…In mouse ovarian granulosa cells Chen et al [ 96 ] and Zhang et al [ 97 ] demonstrated by MTT, EdU and flow cytometry that ZEA suppressed in vitro cell viability at 30–150 μM and increased apoptosis at 15–60 μM after 24 or 72h of exposure. Close to the results recorded by Song et al [ 95 ] in pig (a decreased of cell proportion in the S and G2 phase at ZEA 80 µmol/L), Zhang et al [ 97 ], found that mouse granulosa cells were arrested in G1 phase of cell cycle and the cells proportion decreased in phase S and G2 after 30 μM ZEA treatment. However, in another study this author [ 98 ] found species specific ZEA effect, pig being more sensitive than mouse.…”
Section: Effect Of Zearalenone On Adaptive Immune Responsesupporting
confidence: 65%
“…In weaned piglets, ZEA (0.5, 1.0 and 1.5 mg/kg) induces ovarian development by accelerating ovarian follicles proliferation through the activation of ERs/GSK-3β-dependent Wnt-1/β-catenin signaling pathway [ 94 ]. Also, ZEA (0.5–1.5 mg/kg) determined an abnormal uterine proliferation through TGF signaling pathway [ 95 ]. Investigating other regulatory pathways involved by ZEA in uterine hypertrophy, these authors exposed porcine endometrial epithelial cells to ZEA 0, 5, 20 and 80 μmol/L for 24 h and cell cycle was analyzed.…”
Section: Effect Of Zearalenone On Adaptive Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In pig endometrial stromal cells, β-ZOL altered transcription of cell cycle-dependent kinases and reduced phosphorylation of MAPK and AKT (PKB) kinases [ 119 ]. Additionally, recent studies in porcine endometrial cells indicate that ZEN can activate the WNT/β-catenin signaling pathway to promote proliferation [ 123 ]. Overall, the evidence from murine models points toward strong apoptotic effects of mycoestrogens in the uterus and decreased cell viability in endometrial stromal and granulosa porcine-derived cells [ 101 , 118 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the relative mRNA and protein expressions of proliferating cell nuclear antigen (PCNA), BCL-2 associated X protein (BAX), and B-cell lymphoma/leukemia-2 (BCL-2) were up-regulated through the TGF-β1/Smad3 signaling pathway in uteri of gilts fed 1.5 mg/kg of a ZEA-contaminated diet [ 12 ]. Changes of relative mRNA and protein expressions of GSK-3 and Cyclin D1 of the Wnt/β-catenin signaling pathway in ZEA-treated porcine endometrial epithelial cells were also observed [ 13 ]. However, the potential physiological differences and certain molecular mechanisms of ZEA-induced uterine hypertrophy are unclear.…”
Section: Introductionmentioning
confidence: 99%